Degradable PLA composite material and preparation method thereof
By blending end carboxy-hyperbranched polycaprolactone and adding potassium titanate whiskers in polylactic acid materials, the block copolymer and crosslinking network structure is formed, and the problems of large brittleness and poor heat resistance of polylactic acid materials are solved, and the flexibility and heat resistance of the material are significantly improved.
Patent Information
- Application Number
- CN202510146662.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-02-10
AI Technical Summary
Polylactic acid materials have problems such as high brittleness and poor heat resistance, which limits their application range.
The block copolymer and crosslinking network structure are formed by blending end carboxy hyperbranched polycaprolactone with polylactic acid and adding potassium titanate whiskers to the composite material to form a block copolymer and crosslinking network structure to improve the flexibility and heat resistance of the material.
It significantly improves the impact resistance and flexibility of polylactic acid composite materials, while also improving the heat resistance and mechanical properties of the materials, solving the problem of high brittleness of polylactic acid materials.
Smart Images

Figure BDA0005266741020000081 
Figure BDA0005266741020000091 
Figure BDA0005266741020000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polylactic acid materials, and particularly relates to a degradable PLA composite material and a preparation method thereof. Background Art
[0002] With the increasing pollution of the environment caused by plastics and the continuous consumption of oil resources, it is urgent to develop green, environmentally friendly and renewable biodegradable materials. Polylactic acid (PLA) is a new type of green biomaterial that is completely degradable. It has good biocompatibility, degradability and physical and mechanical properties. It can be processed by various processes such as injection molding, extrusion, spinning, etc. to prepare different degradable plastic products. It is widely used in many fields such as clothing, packaging, agriculture, automobiles, electronics, biomedicine and engineering.
[0003] However, polylactic acid has defects such as brittleness, poor heat resistance, and low melt strength. Pure polylactic acid often breaks brittlely when subjected to external forces at room temperature, and changes in the production process cannot significantly improve its mechanical properties, thus limiting the application range of polylactic acid. Therefore, it is urgent to develop a material that can overcome defects such as poor toughness and maintain degradability to meet the application requirements in various fields. Summary of the invention
[0004] The purpose of the present invention is to provide a degradable PLA composite material and a preparation method thereof, so as to solve the problems of high brittleness and poor heat resistance of polylactic acid materials.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] In a first aspect, the present invention provides a degradable PLA composite material, comprising the following raw materials in parts by weight:
[0007] 80-95 parts of polylactic acid;
[0008] 5 to 15 parts of carboxyl-terminated hyperbranched polycaprolactone;
[0009] Potassium titanate whiskers 3-5 parts;
[0010] 0.1 to 3 parts of antioxidant;
[0011] 1 to 5 parts of compatibilizer;
[0012] 1 to 2 parts of anti-hydrolysis agent.
[0013] Preferably, the compatibilizer is an epoxy-reactive compatibilizer.
[0014] More preferably, the compatibilizer is an ADR compatibilizer.
[0015] Preferably, the polylactic acid is L-polylactic acid.
[0016] Preferably, the antioxidant includes a combination of one or more of antioxidant 1010 , antioxidant 1790 , antioxidant 1076 , antioxidant 168 , and antioxidant 626 .
[0017] Preferably, the anti-hydrolysis agent includes a combination of one or more of a monomeric carbodiimide anti-hydrolysis agent and a polymeric carbodiimide anti-hydrolysis agent.
[0018] By adopting the above technical scheme, polycaprolactone has good flexibility and excellent processing performance. After blending with polylactic acid, it can significantly improve the flexibility of polylactic acid. Compared with general linear polycaprolactone, hyperbranched polycaprolactone has more flexible long chains and ester groups, high mobility between molecular chains, higher flexibility and flexibility, and combined with the highly branched structure of hyperbranched polyester, the toughening effect of polycaprolactone on polylactic acid can be further improved.
[0019] The polarity of hyperbranched polycaprolactone is also improved compared to polycaprolactone, and the dispersibility in polylactic acid is enhanced, and the hyperbranched polycaprolactone of the present invention is also treated by carboxylation, and the terminal carboxyl group in the obtained hyperbranched polyester and the terminal hydroxyl group of polylactic acid can undergo a ring-opening reaction with the epoxy group of the epoxy reactive compatibilizer adopted in the present invention, thereby generating a block copolymer in situ, linking the polylactic acid matrix and the terminal carboxyl hyperbranched polycaprolactone in the system, and then improving the interfacial adhesion of the two phases, playing the effect of volume increase, and strengthening the interfacial bonding force of polylactic acid and the terminal carboxyl hyperbranched polyester. In addition, the hyperbranched structure of the terminal carboxyl hyperbranched polycaprolactone can form a certain cross-linked three-dimensional network structure in the system, and when subjected to external force impact, it can absorb impact energy, improve the impact resistance of the material, thereby improving the problem of large brittleness of polylactic acid, and enhancing the flexibility of the composite material. In addition, the carboxyl-terminated hyperbranched polycaprolactone is a biodegradable material, which will not affect the degradable properties of the polylactic acid composite material and can also regulate the degradation rate of the polylactic acid to a certain extent.
[0020] However, the tensile strength of the polylactic acid modified by the terminal carboxyl hyperbranched polycaprolactone composite is reduced, and since the terminal carboxyl hyperbranched polycaprolactone itself has general heat resistance, the heat resistance of the composite material is not improved after being composited with polylactic acid, and due to the influence on the crystallization properties of polylactic acid, the heat resistance of the composite material is further reduced. In order to improve this problem, potassium titanate whiskers are further added to the composite material of the present invention. Potassium titanate whiskers themselves have very high strength, as well as excellent chemical stability and thermal stability. After being mixed with polylactic acid, the tensile strength and thermal stability of the material can be significantly improved.
[0021] In addition, the fine-sized potassium titanate whiskers can act as heterogeneous nucleating agents for polylactic acid materials, providing additional nucleation sites for polylactic acid molecular chains, reducing the energy barrier required for crystallization, and promoting the crystallization process of polylactic acid; and the high aspect ratio of potassium titanate whiskers also promotes the formation of an ordered structure inside the polylactic acid system, thereby improving the crystallinity of the polylactic acid composite material, thereby improving the heat resistance of the polylactic acid composite material.
[0022] Preferably, the raw materials of the carboxyl-terminated hyperbranched polycaprolactone include hyperbranched polycaprolactone and dianhydride in a molar ratio of 1:(12-15).
[0023] Preferably, the raw material of the hyperbranched polycaprolactone comprises 2,2-dimethylolpropionic acid and caprolactone in a molar ratio of 1:(20-22).
[0024] More preferably, the hyperbranched polycaprolactone is prepared according to the following method:
[0025] 2,2-dihydroxymethylpropionic acid and caprolactone are mixed, a tin catalyst is added, the temperature is increased to 100-120° C. under a nitrogen atmosphere, the mixture is stirred for reaction for 2-3 hours, the temperature is increased to 145-150° C. under vacuum conditions, the mixture is stirred for reaction for 4-5 hours, the temperature is further increased to 170-180° C., the mixture is stirred for reaction for 12-15 hours, and then standing, dissolving, precipitating and drying are performed to obtain hyperbranched polycaprolactone.
[0026] Preferably, the tin catalyst comprises a combination of one or more of stannous octoate and dibutyltin dilaurate; the amount of the tin catalyst added is 0.02-0.1 wt % of the mass of caprolactone.
[0027] Preferably, the dianhydride includes a combination of one or more of succinic anhydride, maleic anhydride, phthalic anhydride and adipic anhydride.
[0028] Preferably, the carboxyl-terminated hyperbranched polycaprolactone is prepared according to the following method: hyperbranched polycaprolactone and dianhydride are added to a solvent, the temperature is raised to 85-95° C. after mixing, the reaction is stirred until the acid value of the system becomes constant, and then the reaction is stopped, and then the carboxyl-terminated hyperbranched polycaprolactone is obtained by precipitation and drying.
[0029] Preferably, the solvent includes a combination of one or more of dibenzoylmethane, N,N-dimethylformamide and N-methylpyrrolidone.
[0030] By adopting the above technical scheme, the present invention obtains carboxyl-terminated hyperbranched polycaprolactone by reacting between dianhydride and the hydroxyl group on the hyperbranched polycaprolactone molecular chain. The hyperbranched polycaprolactone treated with carboxylation introduces more multivariate polar groups on the molecular chain, and can form intermolecular forces with the polar groups in polylactic acid, and the intermolecular interactions can improve the binding force and dispersibility of the carboxyl-terminated hyperbranched polycaprolactone in polylactic acid. In the preparation process, the carboxyl-terminated hyperbranched polycaprolactone can be evenly distributed in the polylactic acid matrix, and react and link with the compatibilizer, thereby improving the compatibility and interfacial bonding force between the two; More active sites also form a stable network structure inside the material, thereby improving the ductility of the composite material, showing higher impact properties and comprehensive mechanical properties.
[0031] And through the reaction between the terminal carboxyl hyperbranched polycaprolactone and the compatibilizer, the processing performance of the polylactic acid composite material is also improved, the fluidity is improved, which helps to improve the molding efficiency, reduce the internal defects of the material, and thus improve the toughness of the material. The introduction of carboxyl groups can also control the biodegradation behavior of the polylactic acid composite material. Since carboxyl groups can accelerate the hydrolysis reaction, the degradation rate of the obtained PLA composite material is increased and the rate is controllable.
[0032] Preferably, the potassium titanate whiskers are modified by sodium lignin sulfonate.
[0033] Preferably, the mass ratio of potassium titanate whiskers to sodium lignin sulfonate is 1:(0.02-0.06).
[0034] Preferably, potassium titanate whiskers are modified by the following method: sodium lignin sulfonate is dissolved in deionized water, potassium titanate whiskers and an acid catalyst are added, stirred and dispersed, and immersed for 8 to 12 hours, and then centrifuged, washed, dried and ground to obtain modified potassium titanate whiskers.
[0035] Preferably, the acidic catalyst comprises a combination of one or more of p-toluenesulfonic acid, sulfuric acid, hydrochloric acid and phosphoric acid; the amount of the acidic catalyst added is 0.01 to 0.05 wt % of the mass of the potassium titanate whisker.
[0036] Potassium titanate whiskers have a small particle size and are prone to agglomeration or bridging during processing, which affects the uniform dispersion of potassium titanate whiskers in polylactic acid composites. As a reinforcing phase, the uneven distribution of potassium titanate whiskers in polylactic acid composites will cause the performance of the composites to decline and the uniformity of processing and manufacturing to be poor. Therefore, it is necessary to perform surface modification on potassium titanate whiskers.
[0037] By adopting the above technical scheme, the present invention uses sodium lignin sulfonate to perform surface treatment on potassium titanate whiskers, using deionized water as a medium, and the sulfonic acid groups in the sodium lignin sulfonate can react and connect with the hydroxyl groups on the surface of the potassium titanate whiskers, or form intermolecular forces such as hydrogen bonds, and the sodium lignin sulfonate is connected to the surface of the potassium titanate whiskers. On the one hand, the molecular chain of sodium lignin sulfonate can form a spatial three-dimensional barrier in the potassium titanate whiskers, hindering the mutual attraction and agglomeration between the potassium titanate whiskers, and improving the dispersibility of the potassium titanate whiskers in the polylactic acid matrix; on the other hand, sodium lignin sulfonate is obtained by sulfonation modification of natural high molecular polymer lignin, has biodegradable properties, and will not affect the biodegradability of the polylactic acid composite material.
[0038] Moreover, after the modification treatment with sodium lignin sulfonate, a large number of polar groups such as sulfonic acid groups are introduced on the surface of potassium titanate whiskers, which can further improve the binding force of potassium titanate whiskers in polylactic acid composite materials, and will not precipitate during use. In addition, it can participate in the construction of a three-dimensional cross-linked network between terminal carboxyl hyperbranched polycaprolactone and polylactic acid, thereby improving the mechanical properties of the material. At the same time, since the main chain molecule of sodium lignin sulfonate is the basic skeleton of lignin, it has a certain rigidity and participates in the cross-linked network structure, which can improve the heat resistance of polylactic acid composite materials.
[0039] In a second aspect, the present invention provides a method for preparing a degradable PLA composite material, comprising the following process steps:
[0040] S1. Drying the polylactic acid at 60-80°C for 6-8h;
[0041] S2. Weigh the dried polylactic acid, carboxyl-terminated hyperbranched polycaprolactone, potassium titanate whiskers, a compatibilizer, an antioxidant and an anti-hydrolysis agent according to the corresponding mass fractions, and stir and mix for 10 to 30 minutes to obtain a mixed material;
[0042] S3. The mixed material is melt-plasticized and extruded into granules to obtain a degradable PLA composite material.
[0043] Preferably, the melt plasticization temperature is 190-210°C.
[0044] Beneficial effects of the present invention:
[0045] 1. The present invention adopts carboxyl-terminated hyperbranched polycaprolactone composite polylactic acid, which can significantly improve the impact resistance of the material and improve the problem of large brittleness of polylactic acid material. The hyperbranched structure increases the content of flexible molecular chains, improves the ability to absorb external impact energy, and enhances the flexibility of polylactic acid composite materials. In addition, hyperbranched polycaprolactone is treated with carboxylation to improve the polarity of polycaprolactone, thereby improving the dispersibility in the matrix, and the terminal carboxyl group and the terminal hydroxyl group in the polylactic acid can react with the epoxy reactive compatibilizer in the system, thereby improving the interfacial bonding force of the two, improving compatibility, and the formed cross-linked network structure can help better improve the mechanical properties of the material.
[0046] 2. Potassium titanate whiskers are also added to the composite material of the present invention, which can make up for the problems of decreased tensile strength and poor heat resistance caused by the addition of terminal carboxyl hyperbranched polycaprolactone. In order to further improve the improvement effect of potassium titanate whiskers, the potassium titanate whiskers are modified with sodium lignin sulfonate to improve the dispersibility of potassium titanate whiskers in the polylactic acid matrix, and participate in the formation of a cross-linked network, further improving the heat resistance and mechanical properties of the composite material, and will not affect the degradability of the material. DETAILED DESCRIPTION
[0047] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] Preparation Example
[0049] Preparation Example 1 Carboxyl-terminated hyperbranched polycaprolactone
[0050] Preparation Example 1-1, a carboxyl-terminated hyperbranched polycaprolactone, prepared according to the following method:
[0051] 2,2-Dihydroxymethylpropionic acid and caprolactone were mixed in a molar ratio of 1:20, 1.5 g of stannous octoate was added, the temperature was raised to 120°C under a nitrogen atmosphere, the reaction was stirred for 2 hours, the temperature was raised to 150°C under vacuum conditions, the reaction was stirred for 5 hours, the temperature was further raised to 180°C, the reaction was stirred for 12 hours, and then the hyperbranched polycaprolactone was obtained by standing, dissolving, precipitating and drying.
[0052] The hyperbranched polycaprolactone and succinic anhydride obtained above are added to N,N-dimethylformamide in a molar ratio of 1:13, and the temperature is raised to 85-95°C after mixing. The reaction is stirred until the acid value of the system becomes constant and then the reaction is stopped. The carboxyl-terminated hyperbranched polycaprolactone is obtained by precipitation and drying.
[0053] Preparation Example 1-2, a carboxyl-terminated hyperbranched polycaprolactone, is different from Preparation Example 1-1 only in that the molar ratio of 2,2-dimethylolpropionic acid to caprolactone is 1:22; and the molar ratio of hyperbranched polycaprolactone to succinic anhydride is 1:12.
[0054] Preparation Example 1-3, a carboxyl-terminated hyperbranched polycaprolactone, is different from Preparation Example 1-1 only in that the molar ratio of the hyperbranched polycaprolactone to succinic anhydride is 1:15.
[0055] Preparation Example 1-4, a carboxyl-terminated hyperbranched polycaprolactone, is different from Preparation Example 1-1 only in that the molar ratio of the hyperbranched polycaprolactone to succinic anhydride is 1:10.
[0056] Preparation Example 1-5, a carboxyl-terminated hyperbranched polycaprolactone, is different from Preparation Example 1-1 only in that the molar ratio of the hyperbranched polycaprolactone to succinic anhydride is 1:16.
[0057] Preparation Example 1-6, a hyperbranched polycaprolactone, was prepared according to the following method:
[0058] 2,2-Dihydroxymethylpropionic acid and caprolactone were mixed in a molar ratio of 1:20, 1.5 g of stannous octoate was added, the temperature was raised to 120°C under a nitrogen atmosphere, the reaction was stirred for 2 hours, the temperature was raised to 150°C under vacuum conditions, the reaction was stirred for 5 hours, the temperature was further raised to 180°C, the reaction was stirred for 12 hours, and then the hyperbranched polycaprolactone was obtained by standing, dissolving, precipitating and drying.
[0059] Preparation Example 2 Modification of Potassium Titanate Whiskers
[0060] Preparation Example 2-1: A potassium titanate whisker is modified according to the following method:
[0061] 0.4 g of sodium lignin sulfonate was dissolved in 100 mL of deionized water, 10 g of potassium titanate whiskers (with a diameter of 0.1 to 0.3 μm) and 0.003 g of hydrochloric acid were added, stirred and dispersed, and immersed for 10 hours, and then centrifuged, washed, dried and ground to obtain modified potassium titanate whiskers.
[0062] Preparation Example 2-2, a potassium titanate whisker, is different from Preparation Example 2-1 only in that the added amount of sodium lignin sulfonate is 0.2 g.
[0063] Preparation Example 2-3, a potassium titanate whisker, is different from Preparation Example 2-1 only in that the added amount of sodium lignin sulfonate is 0.6 g.
[0064] Preparation Example 2-4: A potassium titanate whisker is modified according to the following method:
[0065] 0.4 g of γ-glycidyloxypropyltrimethoxysilane was mixed with deionized water to obtain an aminosilane coupling agent hydrolyzate, wherein the mass ratio of deionized water to phthalate coupling agent was 7:1; 10 g of potassium titanate whiskers were dispersed in 100 nL of methanol solution, the aminosilane coupling agent hydrolyzate was added, and the mixture was stirred for 6 hours, followed by centrifugation, washing and drying to obtain modified potassium titanate whiskers.
[0066] Example
[0067] Example 1, a degradable PLA composite material, prepared according to the following method:
[0068] S1. Drying L-polylactic acid (weight average molecular weight of 10,000 to 200,000 g / mol) at 80°C for 6 h;
[0069] S2. Weigh 9 kg of dried polylactic acid, 1 kg of the carboxyl-terminated hyperbranched polycaprolactone prepared in Preparation Example 1-1, 0.4 kg of potassium titanate whiskers (diameter 0.1 to 0.3 μm), 0.3 kg of ADR compatibilizer, 0.2 kg of antioxidant (including antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1) and 0.1 kg of monomeric carbodiimide anti-hydrolysis agent, and stir and mix for 20 min to obtain a mixed material;
[0070] S3. The mixed material is melt-plasticized and extruded into granules to obtain a degradable PLA composite material, wherein the melt-plasticization temperature is 200°C.
[0071] Example 2 and Example 3 are degradable PLA composite materials. The only difference from Example 1 is that the ratio of the raw materials is adjusted, as shown in Table 1:
[0072] Table 1 Formula table of Example 1 to Example 3
[0073]
[0074]
[0075] The carboxyl-terminated hyperbranched polycaprolactones used are all the carboxyl-terminated hyperbranched polycaprolactones prepared in Preparation Example 1-1.
[0076] Example 4, a degradable PLA composite material, is different from Example 1 only in that the carboxyl-terminated hyperbranched polycaprolactone prepared in Preparation Example 1-1 is replaced by an equal amount of the carboxyl-terminated hyperbranched polycaprolactone prepared in Preparation Example 1-2.
[0077] Example 5, a degradable PLA composite material, is different from Example 1 only in that the carboxyl-terminated hyperbranched polycaprolactone prepared in Preparation Example 1-1 is replaced by an equal amount of the carboxyl-terminated hyperbranched polycaprolactone prepared in Preparation Example 1-3.
[0078] Example 6, a degradable PLA composite material, is different from Example 1 only in that the carboxyl-terminated hyperbranched polycaprolactone prepared in Preparation Example 1-1 is replaced by an equal amount of the carboxyl-terminated hyperbranched polycaprolactone prepared in Preparation Example 1-4.
[0079] Example 7, a degradable PLA composite material, is different from Example 1 only in that the carboxyl-terminated hyperbranched polycaprolactone prepared in Preparation Example 1-1 is replaced by an equal amount of the carboxyl-terminated hyperbranched polycaprolactone prepared in Preparation Example 1-5.
[0080] Example 8, a degradable PLA composite material, is different from Example 1 only in that the potassium titanate whiskers are replaced with an equal amount of the potassium titanate whiskers prepared in Preparation Example 2-1.
[0081] Example 9, a degradable PLA composite material, is different from Example 8 only in that the potassium titanate whiskers prepared in Preparation Example 2-1 are replaced by an equal amount of potassium titanate whiskers prepared in Preparation Example 2-2.
[0082] Example 10, a degradable PLA composite material, is different from Example 8 only in that the potassium titanate whiskers prepared in Preparation Example 2-1 are replaced by an equal amount of potassium titanate whiskers prepared in Preparation Example 2-3.
[0083] Example 11, a degradable PLA composite material, is different from Example 8 only in that the potassium titanate whiskers prepared in Preparation Example 2-1 are replaced by an equal amount of potassium titanate whiskers prepared in Preparation Example 2-4.
[0084] Comparative Example
[0085] Comparative Example 1 is a degradable PLA composite material, which is different from Example 1 only in that the added amount of the carboxyl-terminated hyperbranched polycaprolactone prepared in Preparation Example 1-1 is 0.2 kg.
[0086] Comparative Example 2, a degradable PLA composite material, is different from Example 1 only in that the added amount of the carboxyl-terminated hyperbranched polycaprolactone prepared in Preparation Example 1-1 is 2 kg.
[0087] Comparative Example 3, a degradable PLA composite material, is different from Example 1 only in that the carboxyl-terminated hyperbranched polycaprolactone prepared in Preparation Example 1-1 is replaced by an equal amount of the carboxyl-terminated hyperbranched polycaprolactone prepared in Preparation Example 1-6.
[0088] Comparative Example 4 is a degradable PLA composite material, which is different from Example 1 only in that the added amount of potassium titanate whiskers is 0.1 kg.
[0089] Comparative Example 5 is a degradable PLA composite material, which is different from Example 1 only in that the added amount of potassium titanate whiskers is 0.6 kg.
[0090] Comparative Example 6, a degradable PLA composite material, is different from Example 1 only in that an equal amount of polycaprolactone (average molecular weight of 10000 g / mol) is used to replace the carboxyl-terminated hyperbranched polycaprolactone prepared in Preparation Example 1-1.
[0091] Comparative Example 7, a degradable PLA composite material, is different from Example 1 only in that the carboxyl-terminated hyperbranched polycaprolactone prepared in Preparation Example 1-1 is not added.
[0092] Comparative Example 8 is a degradable PLA composite material, which is different from Example 1 only in that potassium titanate whiskers are not added.
[0093] Comparative Example 9, a degradable PLA composite material, which differs from Example 1 only in that an equal amount of POM compatibilizer (density of 1.1-1.3 g / cm 3 ) replaces the ADR compatibilizer.
[0094] Performance testing
[0095] 1. Mechanical properties test:
[0096] (1) Tensile property test: According to the relevant records in GB / T 1040.2-2022 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics", the tensile strength and elongation at break of the PLA composite materials obtained in the examples and comparative examples were tested.
[0097] (2) Impact performance test: According to the relevant records in GB / T 1843-2008 "Determination of Izod Impact Strength of Plastics", the impact strength of the PLA composite materials obtained in the examples and comparative examples was tested. The above test results are shown in Table 2.
[0098] 2. Heat resistance test: According to the relevant records in ISO 75-2:2013 "Determination of deformation temperature of plastics under load Part 2: Plastics and hard rubber", the heat deformation temperature of the PLA composite materials obtained in the examples and comparative examples was tested under the conditions of 0.45 MPa load and 120°C / h. The test results are shown in Table 3.
[0099] Table 2 Mechanical properties test results
[0100]
[0101] Table 3 Heat resistance test results
[0102]
[0103]
[0104] According to Table 2 and Table 3, in combination with Example 1 and Example 2 to Example 5, it can be seen that the mechanical properties and heat resistance of Example 2 to Example 5 are not significantly changed compared with Example 1. The difference between Example 2 to Example 5 and Example 1 is only that the raw materials and the raw material ratio are adjusted within the required range, and the performance of the obtained PLA composite material is not significantly changed compared with Example 1.
[0105] In combination with Example 1, Example 6, Example 7 and Comparative Example 3, it can be seen that the elongation at break and impact strength of Example 6, Example 7 and Comparative Example 3 are reduced compared with those of Example 1, and the heat deformation temperature is reduced, wherein the reduction in Comparative Example 3 is more obvious, indicating that the mechanical properties and heat resistance of Example 6, Example 7 and Comparative Example 3 are reduced compared with those of Example 1. The reason is that the difference between Example 6, Example 7 and Comparative Example 3 compared with Example 1 is only that the terminal carboxyl content of the carboxyl-terminated hyperbranched polycaprolactone used is changed outside the required range, wherein the carboxyl content in Example 6 is reduced, the number of active groups reacting with the compatibilizer is reduced, the dispersibility in polylactic acid is reduced, the cross-linked network density formed is reduced, and the improvement effect on various properties of the material is reduced, while no carboxylation treatment is performed in Comparative Example 3, and the performance reduction is more significant; in Example 7, the degree of carboxylation is increased, and the large amount of polar groups introduced will increase the attraction between the carboxyl-terminated hyperbranched polycaprolactones, and agglomeration is easily caused, the dispersibility in the polylactic acid matrix is reduced, and the performance of the material is reduced.
[0106] In combination with Example 1, Example 8, and Example 9 to Example 11, it can be seen that the tensile strength and heat deformation temperature of Example 8 are improved compared with Example 1, and the changes in Example 9 and Example 10 are not obvious compared with Example 8, and the performance improvement of Example 11 is not obvious compared with Example 1. The reason is that the difference between Example 8 and Example 1 is that the potassium titanate whiskers used are modified with sodium lignin sulfonate, and the dispersibility of potassium titanate whiskers in the polylactic acid matrix is significantly increased, and the introduction of sodium lignin sulfonate molecular chains can also participate in the formation of the cross-linked network, and its rigid skeleton can also improve the heat resistance of the material, and will not affect the biodegradability. The difference between Example 9 and Example 10 compared with Example 8 is only that the addition amount of the modifier sodium lignin sulfonate is changed within the required range, and the effect on the performance is not obvious. In Example 11, the potassium titanate whiskers are modified with a silane coupling agent, which can also improve a certain degree of dispersibility, but it does not help to improve the flexibility and heat resistance of the material.
[0107] In combination with Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 7, it can be seen that the mechanical properties and heat resistance of Comparative Example 1, Comparative Example 2 and Comparative Example 7 are all reduced compared to Example 1, and the reduction in Comparative Example 7 is the most obvious. The reason is that the difference between Comparative Example 1, Comparative Example 2 and Comparative Example 7 compared to Example 1 is only that the addition amount of terminal carboxyl hyperbranched polycaprolactone is adjusted, and the addition amount of terminal carboxyl hyperbranched polycaprolactone is reduced in Comparative Example 1, resulting in a significant reduction in the flexible segment in the polylactic acid composite material, which will reduce the flexibility and impact resistance of the material, and no terminal carboxyl hyperbranched polycaprolactone is added in Comparative Example 7, and the performance degradation is more obvious. In Comparative Example 2, the addition amount of terminal carboxyl hyperbranched polycaprolactone is increased, and the large amount of introduction of hyperbranched structure and polar groups will increase the cross-linking structure density, reduce the free activity performance of the molecular chain, and is not conducive to the improvement of flexibility.
[0108] Combining Example 1, Comparative Example 4, Comparative Example 5 and Comparative Example 8, it can be seen that the mechanical properties and heat resistance of Comparative Example 4, Comparative Example 5 and Comparative Example 8 are all reduced compared with Example 1, and the reduction in Comparative Example 8 is the most obvious. The reason is that the difference between Comparative Example 4, Comparative Example 5 and Comparative Example 8 and Example 1 is only that the amount of potassium titanate whiskers added is adjusted, wherein the amount of potassium titanate whiskers added is reduced in Comparative Example 4, and the effect of improving the tensile strength of the composite material is reduced, and the lack of potassium titanate whiskers as a nucleating agent for heterogeneous nucleation of polylactic acid reduces the heat resistance of the composite material. Potassium titanate whiskers are not added in Comparative Example 8, and the tensile strength and heat resistance decrease more significantly. The amount of potassium titanate whiskers added is increased in Comparative Example 5, and excessive addition will cause agglomeration between small-sized potassium titanate whiskers, which will affect the processing performance and affect the improvement of the mechanical properties and heat resistance of the material.
[0109] Combining Example 1 and Comparative Example 6, it can be seen that the mechanical properties and heat resistance of Comparative Example 6 are significantly reduced compared with Example 1. The reason is that linear polycaprolactone is used in Comparative Example 6. On the one hand, it lacks a hyperbranched structure, and the absorption effect of the composite material on impact capacity is reduced, and the impact resistance of the material is reduced; on the other hand, polycaprolactone is a non-polar polymer and has poor compatibility with polylactic acid. The reactivity between polycaprolactone and the compatibilizer is very low, and the interfacial bonding force between the two cannot be improved. It is also difficult to form a stable cross-linked network, and the performance of the material is reduced accordingly.
[0110] Combining Example 1 and Comparative Example 9, it can be seen that the mechanical properties and heat resistance of Comparative Example 9 are lower than those of Example 1. The reason is that the compatibilizer used in Comparative Example 9 is a non-reactive compatibilizer. Although it can increase the compatibility between the terminal carboxyl hyperbranched polycaprolactone and the polylactic acid to a certain extent, compared with the reactive compatibilizer, the two are only combined by intermolecular forces rather than forming a block copolymer, which can significantly increase the binding force between the two, and is less affected by external forces, and cannot help the composite material form a stable cross-linked network structure, so the performance is reduced.
[0111] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0112] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A degradable PLA composite material, characterized in that: Including the following raw materials by mass: 80-95 parts of polylactic acid; 5 to 15 parts of carboxyl-terminated hyperbranched polycaprolactone; Potassium titanate whiskers 3-5 parts; 0.1 to 3 parts of antioxidant; 1 to 5 parts of compatibilizer; 1 to 2 parts of anti-hydrolysis agent.
2. The degradable PLA composite material according to claim 1, characterized in that: The raw materials of the carboxyl-terminated hyperbranched polycaprolactone include hyperbranched polycaprolactone and dianhydride in a molar ratio of 1:(12-15).
3. The degradable PLA composite material according to claim 2, characterized in that: The raw materials of the hyperbranched polycaprolactone include 2,2-dihydroxymethyl propionic acid and caprolactone in a molar ratio of 1:(20-22).
4. The degradable PLA composite material according to claim 2, characterized in that: The dianhydride includes one or more of succinic anhydride, maleic anhydride, phthalic anhydride and adipic anhydride.
5. The degradable PLA composite material according to claim 2, characterized in that: The carboxyl-terminated hyperbranched polycaprolactone is prepared according to the following method: hyperbranched polycaprolactone and dianhydride are added to a solvent, the temperature is raised to 85-95° C. after mixing, the reaction is stirred until the acid value of the system is constant, and then the reaction is stopped, and then the carboxyl-terminated hyperbranched polycaprolactone is obtained through precipitation and drying.
6. The degradable PLA composite material according to claim 1, characterized in that: The potassium titanate whiskers are modified by sodium lignin sulfonate.
7. The degradable PLA composite material according to claim 6, characterized in that: The mass ratio of the potassium titanate whisker to the sodium lignin sulfonate is 1:(0.02-0.06).
8. The degradable PLA composite material according to claim 6, characterized in that: The potassium titanate whisker is modified according to the following method: sodium lignin sulfonate is dissolved in deionized water, potassium titanate whisker and acid catalyst are added, stirred and dispersed and immersed for 8 to 12 hours, and then centrifuged, washed, dried and ground to obtain modified potassium titanate whisker.
9. The degradable PLA composite material according to claim 1, characterized in that: The compatibilizer is an epoxy reactive compatibilizer.
10. A method for preparing a degradable PLA composite material according to any one of claims 1 to 9, characterized in that: The process steps include: S1. Drying the polylactic acid at 60-80°C for 6-8h; S2. Weigh the dried polylactic acid, carboxyl-terminated hyperbranched polycaprolactone, potassium titanate whiskers, a compatibilizer, an antioxidant and an anti-hydrolysis agent according to the corresponding mass fractions, and stir and mix for 10 to 30 minutes to obtain a mixed material; S3. The mixed material is melt-plasticized and extruded into granules to obtain a degradable PLA composite material.
Citation Information
Patent Citations
Process for the Development of Compatibilized Poly(L-co-D-lactic acid) and Polycaprolactone Blends, Compatibilized Poly(L-co-D-lactic acid) and Polycaprolactone Blends and Use Thereof
BR102014023798A2
Polylactic acid composite material and preparation method thereof
CN103113730A
Wear-resistant polycaprolactone composite material
CN109694560A
Method for preparing high-performance and high-fluidity polylactic acid based on hyperbranched polymer
CN112694730A
Preparation method and application of modified polylactic acid fiber
CN118773766A
Cited By
Self-degradation reservoir protection temporary plugging agent suitable for unconventional reservoir as well as preparation method and application of self-degradation reservoir protection temporary plugging agent
CN120442228A
Degradable environment-friendly suction nozzle based on PLA / PBS composite material and preparation method of degradable environment-friendly suction nozzle
CN121343341A
Preparation process of self-healing dielectric layer of circuit board
CN121699339A